2009
DOI: 10.1245/s10434-009-0618-y
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Alpha-Fetoprotein and Des-γ-Carboxy Prothrombin in Patients with Hepatocellular Carcinoma Undergoing Hepatectomy

Abstract: DCP is a more accurate, albeit complementary, HCC marker than AFP. While the levels of both markers increased with advancing tumor growth, no specific associations were found. The marker values at recurrence indicated the type of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 32 publications
10
105
2
Order By: Relevance
“…Since the 1980s, several novel tumor markers specific for HCC have been widely investigated, and numerous studies demonstrated that the Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) and Golgi protein 73 (GP73) were superior to AFP for the early diagnosis of HCC (Marrero et al, 2005;Durazo et al, 2008;Mao et al, 2010;Toyoda et al, 2011;Witjes et al, 2013), and they also could be used to monitor the response of patients to curative treatment and estimate the risk of relapse (Toyoda et al, 2008;Yamamoto et al, 2009;Mao et al, 2010;Nouso et al, 2011). However, most of these statistics were reported from Japan, and liver resection was the most commonly used curative treatment.…”
Section: Prognosticmentioning
confidence: 99%
“…Since the 1980s, several novel tumor markers specific for HCC have been widely investigated, and numerous studies demonstrated that the Lens culinaris agglutinin-reactive fraction of AFP (AFP-L3) and Golgi protein 73 (GP73) were superior to AFP for the early diagnosis of HCC (Marrero et al, 2005;Durazo et al, 2008;Mao et al, 2010;Toyoda et al, 2011;Witjes et al, 2013), and they also could be used to monitor the response of patients to curative treatment and estimate the risk of relapse (Toyoda et al, 2008;Yamamoto et al, 2009;Mao et al, 2010;Nouso et al, 2011). However, most of these statistics were reported from Japan, and liver resection was the most commonly used curative treatment.…”
Section: Prognosticmentioning
confidence: 99%
“…This tumor marker is regularly used in clinical diagnosis to screen patients with primary HCC and to monitor the recurrence of HCC after curative therapy (15,16). While extensive scientific evidence has been assembled to indicate the clinicopathological significance of DCP, a high level of DCP in the sera of patients with HCC was significantly associated with the presence of vascular invasion followed by the presence of intrahepatic metastasis (16)(17)(18). Thus, DCP may serve to predict a worse prognosis of patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of tumor markers such as AFP and DCP are simple and already widely used for the surveillance and diagnosis of HCC. They are also used to monitor recurrence and serve as prognostic factors following treatments such as curative hepatic resetion (18,19), loco-regional therapy (20) and TACE procedures (21,22). Although numerous studies have reported the relationships between the changes in tu- mor markers during treatment and the antitumor response, there have been no comprehensive reports that have evaluated the relationship between the tumor response and serial changes in AFP and DCP during HAIC using CDDP powder.…”
Section: Discussionmentioning
confidence: 99%